Organic and inorganic fertilization in citrus seedbeds - Koller, Otto Carlos; Boeira, Rita Carla (Pesquisa Agropecuaria Brasileira, 2014)
The effect of mineral and organic fertilizers (poultry house litter, cattle manure and bark of Acacia mearnsii De Wild.) with and without nitrogen coverings, on three citrus seedlings development: Rangpur lime, (Citrus limonia Osbeck), Caipira orange, (C. sinensis (L.) Osbeck) and Poncirus trifoliata (L.) Raf., was evaluated. The field trial was established at Agricultural Experiment Station of Federal University of Rio Grande do Sul, in Guaíba, RS, Brazil, in 1979. The seedlings development of Poncirus trifoliata was more uniform than the other rootstocks. The Rangpur lime attained the greater trunk diameter. On Rangpur lime, the cattle manure treatment with nitrogen coverings improved trurk diameter and height of the plants and the treatment with Acacia mearnsii De Wild. bark was similar to the no-fertilized one in developing this rootstock.